1989
DOI: 10.3168/jds.s0022-0302(89)79392-9
|View full text |Cite
|
Sign up to set email alerts
|

Parturient Hypocalcemia in Jersey Cows Fed Alfalfa Haylage-Based Diets with Different Cation to Anion Ratios

Abstract: Jersey cows were fed three alfalfa haylage-based diets with different cation-anion balances beginning 6 wk preceding third or later calving and ending 24 to 36 h postpartum. Sodium and Cl as percentages of dietary DM were .08 and 1.66 in diet 1 (anionic, 5 cows), .44 and .91 in diet 2 (intermediate, 6 cows), and 1.60 and .34 in diet 3 (cationic, 6 cows). Cation-anion balances were 22, 60, and 126 meq/100 g DM; Ca:P ratios averaged 4:1. Cows fed diet 1 in comparison with cows fed diets 2 or 3 over 6 wk had simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
61
2
10

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 21 publications
15
61
2
10
Order By: Relevance
“…Feeding low Ca-low PO 4 or anionic diets during the dry period tends to reduce hypocalcaemia, while high Ca-high PO 4 or cationic diets tend to induce it (Kichura et al, 1982;Gaynor et al, 1989;Goff et al, 1991). However, the effects of Ca and PO 4 contents in the anionic diet on mineral metabolism are not fully understood.…”
Section: Discussionmentioning
confidence: 97%
“…Feeding low Ca-low PO 4 or anionic diets during the dry period tends to reduce hypocalcaemia, while high Ca-high PO 4 or cationic diets tend to induce it (Kichura et al, 1982;Gaynor et al, 1989;Goff et al, 1991). However, the effects of Ca and PO 4 contents in the anionic diet on mineral metabolism are not fully understood.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, there was a time effect on feed intake, which corresponds with increasing level of anionic salt supplementation. Anionic salts are considered unpalatable (Oetzel et al 1991), and have been shown to depress feed intake in dairy cattle (Tucker et al 1988(Tucker et al , 1992Gaynor et al 1989). The depression in intake appears to be related to alteration of the normal acid-base balance of the animal (Block 1984;Leclerc and Block 1989;Horst et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism of action is that a higher proportion of dietary anions in relation to cations alters the normal acid-base status of the animal causing a mild acidosis. This induces higher Ca excretion in urine, reducing plasma Ca levels, which in turn stimulates Ca homeostatic mechanisms (Gaynor et al 1989;Abu Damir et al 1994). Little published information exists on how diet manipulation (Ca level or feeding of anionic salts) either alone or in combination with vitamin D 3 supplementation influences Ca homeostasis in beef steers.…”
mentioning
confidence: 99%
“…Increased serum concentration of 1,25(OH) 2 D 3 will increase bone resorption with the presence of PTH, in order to maintain plasma Ca (Block, 1984;Gaynor et al, 1989). Dietary supplementation with 25-hydroxyvitamin D (25(OH)D) has been shown to increase both plasma 25(OH)D and 1,25(OH) 2 D 3 concentrations in cattle regardless of the Ca status of the animal (Cho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%